ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR DIGITAL BERBASIS PBL PADA MUATAN PENDIDIKAN PANCASILA KELAS II SEKOLAH DASAR - Dini Hayati, Syifa; Suhailah Fadjrin, Raihan; Satibi Hidayat, Otib; Chandra Utami, Nidya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the need for the development of PBL-based digital picture storybook learning media on the content of Pancasila education. The purpose of this study was to determine the analysis of the needs for developing digital picture storybook media on the content of Pancasila education class II in elementary schools. This research uses the Research and Development (RnD) method using the ADDIE model which focuses on Analysis. The subjects of this study were 1 educator, namely the Class II Teacher and 5 students of class II of Kebon Kosong 17 State Elementary School. The data collection technique in this study used questionnaires and interviews. Based on these questionnaires and interviews, homeroom teachers and students agree and are interested in using digital picture storybook media on the content of Pancasila education. Therefore, it can be concluded that the development of digital picture storybook media on the content of Pancasila education is needed.